Sinergisitas Penataan Ruang (Suatu Penelitian terhadap Kebijakan Pemerintah Provinsi dan Pemerintah Kabupaten/Kota di Aceh) - Efendi Efendi; M. Zuhri M. Zuhri; Mukhlis Mukhlis; M. Iqbal M. Iqbal (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: The purpose of this study is to investigate and explain the form of policies, synergy of government, the appropriateness of policies issued by the provincial and district governments with the authority granted by Act No. 26 of 2007 This research is a normative, legal source material is the primary law materials and secondary legal materials, obtained through field research and library research. Aceh government policies and the policy of local governments has not been able to resolve the border conflict districts. This affects the difficulty of making the border spatial planning policy. Although the provinces and Regency/Municipality in Aceh had formed the Coordinating Agency for Spatial Planning Area (BKTRW), but BKTRW has not functioned optimally. There are no known incompatibilities in spatial planning policy, because local governments are still awaiting the birth of the provincial Qanun. To local governments expected to make policy together adjacent to resolve border issues in spatial planning. Forms of collective wisdom can be shared qanun, joint regulation or collective decisions. In realizing synergy spatial planning in Aceh, the provincial government and Regency/Municipality is expected to optimize the function BKTRW Aceh and BKTRW Regency/Municipality. Synergy Regulation of  Spatial (A Policy Research Provincial Government and Regency/Municipality in Aceh)